OP0152 Effects of Tofacitinib Monotherapy versus Methotrexate on Patient-Reported Outcomes in the 2-Year Phase 3 Oral Start TRIAL in Methotrexate-NaÏVe Patients with Rheumatoid Arthritis. (10th June 2014) - Alten, R.; Strand, V.; Fleischmann, R.; Koncz, T.; Zwillich, S.; Bradley, J.; Gruben, D.; Wilkinson, B.; Krishnaswami, S.; Wallenstein, G.
Abstract : Background: Tofacitinib is a novel, oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: To compare the effects of twice daily (BID) tofacitinib 5 mg and 10 mg monotherapy versus methotrexate (MTX) on patient-reported outcomes (PROs) in the 24-month Phase 3, randomised, double-blind, parallel-group ORAL Start study (NCT01039688 ) in MTX-naïve patients. Results from a 12-month interim analysis have been presented previously [1, 2] here we present the final analysis at 24 months. Methods: MTX-naïve patients with moderate-to-severe active RA were randomised 2:2:1 to receive tofacitinib 5 mg (n=373) or 10 mg BID (n=397), or MTX (n=186) titrated from 10 mg per week to 20 mg per week by Week 8. Secondary PRO endpoints included the mean change from baseline in: Patient Global Assessment of arthritis (PtGA; Visual Analogue Scale [VAS]), pain (VAS), physical function (Health Assessment Questionnaire-Disability Index; HAQ-DI), fatigue (Functional Assessment of Chronic Illness Therapy-Fatigue Scale; FACIT-F), and health-related quality of life (HR-QoL; Short Form 36 version 2, acute; SF-36). Analyses used a linear mixed-effect model with baseline values as covariates in the full analysis set (all randomised patients who received ≥1 dose of study drug and had ≥1 post-baseline measurement). Least squares (LS) mean changes from baseline (±standard error [SE]) and proportions of patients reporting improvements ≥minimum clinically important differences (MCID; no imputation for missing data) in PROs at Month 24 are presented. P-values presented here are with no correction for type I error inflation. Results: A total of 658 patients completed the 24-month study (266, 286, and 106 in the tofacitinib 10 mg and 5 mg and MTX groups, respectively). Over 24 months, significantly (p<0.05) greater improvements from baseline were observed with both tofacitinib 5 and 10 mg BID compared with MTX across the PROs analysed, with the exception of the SF-36 mental component summary score, which was significant at Month 3 but not later (Table 1 ). Compared with MTX, significantly greater proportions of patients receiving tofacitinib 10 mg BID reported changes ≥MCID in all PROs at Month 3, and all PROs, except HAQ-DI, at Months 12 and 24 and FACIT-F at Month 12. Numerically more patients administered tofacitinib 5 mg BID reported changes ≥MCID across PROs versus MTX. Conclusions: In this Phase 3 trial in MTX-naïve patients with RA, tofacitinib 5 and 10 mg BID monotherapy significantly improved multiple PROs over 24 months compared with MTX. References: Lee EB et al. Arthritis Rheum 2012; 64 (Suppl 10): S1049. Strand V et al. Ann Rheum Dis 2013; 72: 252-253. Acknowledgements: Writing support was provided by Erin Bekes PhD, of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: R. Alten Grant/research support: Pfizer Inc, Speakers bureau: Pfizer Inc, V. Strand Consultant for: Pfizer Inc, R. Fleischmann Grant/research support: Pfizer Inc, Consultant for: Pfizer Inc, T. Koncz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Zwillich Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Bradley Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, B. Wilkinson Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Krishnaswami Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, G. Wallenstein Shareholder of: Pfizer Inc, Employee of: Pfizer Inc DOI: 10.1136/annrheumdis-2014-eular.3168